Highly Efficient Reduction of Cr (VI) with C4H6O6 - Hao Peng; Zonghui Qin; Guixuan Jin; Jingjing Wang; Jielin Qin; Lihua Ao; Bing Li (Molecules)
In this paper, tartaric acid (C4H6O6) was used as a reductant to treat chromium (VI)-containing solution. Several independent experimental parameters, including reaction temperature, concentration of H2SO4, concentration of C4H6O6 and reaction time, on the reduction process were studied. The results showed that 100% of the Cr (VI) could be reduced by C4H6O6 in a strong acidic environment under a high reaction temperature. All of the experimental parameters showed positive effects on the reduction process and followed the order [H2SO4] > [C4H6O6] > reaction temperature > reaction time. A higher concentration of tartaric acid and higher reaction temperature could facilitate the reduction process and reduce reaction time.